Use of heat transfer search algorithm while optimizing the process parameters of ECDM to machine quartz material. (2022) - Nema, Aditya; Patel, Vivek; Kumar, Abhishek; Oza, Ankit; Jagani, Ashish B
Abstract: Electrochemical discharge machining (ECDM) provides an effective means to machine materials which shows poor machinability such as glass, carbon fiber, composites, and silica reinforced composites. This paper focuses on optimization of process parameters of ECDM using a non-conventional optimization technique while machining quartz analysis of the effects of variables on the objective function. Micro size holes were generated using tungsten tool with tip size approximately 800 µm. Controlled parameters considered were Feed rate, electrolyte concentration and voltage, while other parameters are kept constant. The design of experiment was done using Box Behnken type response surface methodology. The objective was to maximize the rate of material removal and minimize the rate of tool wear. Optimization was performed such that multiple set of optimal parameters were obtained and any of the obtained results could be adopted as per the required criteria.